Psychotic manifestation in a patient with Wolfram syndrome (DIDMOAD) - Musa, Ramli; NNA, Fatnoon (Malaysian Journal of Psychiatry, 2014)
Wolfram syndrome (WFS) is a rare neurodegerative disorder which is characterized by presentation of diabetes insipidus, juvenile diabetes mellitus, optic atrophy and deafness. We describe a case of WFS with presentation of psychosis. A 17-year-old female presented with psychiatric manifestations, namely inappropriate behaviour and second person auditory hallucination since the age of 16 years. The patient was diagnosed with type 1 diabetes mellitus at the age of 10 years old and subsequently progressive hearing and visual loss a year later. Her ophthalmic evaluation revealed total blindness due to optic atrophy. However she did not have renal dysfunction and diabetes insipidus which are also features of the syndrome. There is scarce literature to describe on psychiatric presentation in WFS. In the past,the psychiatric manifestation which was reported most of times was mood and suicidal behaviour. Hardly any article reported about psychosis (hallucination). We believe, her psychiatric manifestations were related to sensory deprivation due to blindness and deafness caused by the progression of WFS.